Recent advances: role of mycolactone in the pathogenesis and monitoring of Mycobacterium ulcerans infection/Buruli ulcer disease. (January 2016) - Sarfo, Fred Stephen; Phillips, Richard; Wansbrough‐Jones, Mark; Simmonds, Rachel E.
Summary: Infection of subcutaneous tissue with Mycobacterium ulcerans can lead to chronic skin ulceration known as Buruli ulcer. The pathogenesis of this neglected tropical disease is dependent on a lipid‐like toxin, mycolactone, which diffuses through tissue away from the infecting organisms. Since its identification in 1999, this molecule has been intensely studied to elucidate its cytotoxic and immunosuppressive properties. Two recent major advances identifying the underlying molecular targets for mycolactone have been described. First, it can target scaffolding proteins (such as Wiskott Aldrich Syndrome Protein), which control actin dynamics in adherent cells and therefore lead to detachment and cell death by anoikis. Second, it prevents the co‐translational translocation (and therefore production) of many proteins that pass through the endoplasmic reticulum for secretion or placement in cell membranes. These pleiotropic effects underpin the range of cell‐specific functional defects in immune and other cells that contact mycolactone during infection. The dose and duration of mycolactone exposure for these different cells explains tissue necrosis and the paucity of immune cells in the ulcers. This review discusses recent advances in the field, revisits older findings in this context and highlights current developments in structure‐function studies as well as methodology that make mycolactone a promising diagnostic biomarker.